Rancang Bangun Aplikasi Forum Diskusi Pelaut Berbasis Android Menggunakan Metode Extreme Programming di PT Azure Samudera Karsa - Soni Ayi Purnama Purnama (INTERNAL (Information System Journal), 2026)
The need for rapid and structured maritime information exchange within PT Azure Samudera Karsa necessitates a reliable digital communication platform for the seafarer community. This study aims to design and implement a Seafarer Discussion Forum Application using the User-Centered Design approach. The system was developed using the Extreme Programming) methodology, utilizing a Laravel 12-based backend architecture and a Flutter frontend to ensure responsive performance, adaptability to changing requirements, and high-quality coding standards. The research methodology encompasses requirements analysis, system design, iterative coding, and comprehensive testing, including Alpha Testing for functional validation and Beta Testing using the End-User Computing Satisfaction method to evaluate user satisfaction. The results demonstrate that the system operates stably, achieving a user satisfaction score of 84.52%, which indicates a "Very Satisfied" category. Furthermore, the implementation of security features in the release version has successfully enhanced data accountability. In conclusion, the application of the XP methodology has proven effective in delivering a secure, efficient, and adaptive forum application for the seafarer community at PT Azure Samudera Karsa.